The battle for central europe : the siege of szigetvar and the death of suleyman the magnificent and nicholas zrinyi (1566) - Fodor, Pal. (Middle East and Islamic Studies E-Books Online, Collection 2019, ISBN: 9789004386341., 2019)
In The Battle for Central Europe specialists in sixteenth-century Ottoman, Habsburg and Hungarian history provide the most comprehensive picture possible of a battle that determined the fate of Central Europe for centuries. Not only the siege and the death of its main protagonists are discussed, but also the wider context of the imperial rivalry and the empire buildings of the competing great powers of that age. Contributors include Gábor Ágoston, János B. Szabó, Zsuzsa Barbarics-Hermanik, Günhan Börekçi, Feridun M. Emecen, Alfredo Alvar Ezquerra, István Fazekas, Pál Fodor, Klára Hegyi, Colin Imber, Damir Karbić, József Kelenik, Zoltán Korpás, Tijana Krstić, Nenad Moačanin, Gülru Neci̇poğlu, Erol Özvar, Géza Pálffy, Norbert Pap, Peter Rauscher, Claudia Römer, Arno Strohmeyer, Zeynep Tarım, James D. Tracy, Gábor Tüskés, Szabolcs Varga, Nicolas Vatin.